Journal of Modern Power Systems and Clean Energy - Xue, Yusheng
Journal of Modern Power Systems and Clean Energy is dedicated to presenting top-level academic achievements in the fields of modern power systems and clean energy by international researchers and engineers, and is endeavoured to serve as a bridge between Chinese and global researchers in the power industry. Regular articles or letters from both inland and outside China are welcome. The topics focus on modern power systems and clean energy including: • Renewable power generation and clean energy technologies • Distributed energy resources and storage • Modern power system operation and planning • Power system protection and automation in energy management systems • Power system economics and markets • Transmission technologies in modern power systems • Active distribution networks and microgrid applications • Modern power grid devices, sensors and wireless technologies • Load management and customer participation • Electric vehicles and electrification of transportation industry • Cyber-physical systems and power system communication technologies • Interdependency of electricity with other large Infrastructures • Power system modeling and computational analyses • Power system research, education and workforce development.